2017
DOI: 10.1002/acn3.489
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in LRRK2 G2019S and idiopathic Parkinson's Disease

Abstract: ObjectiveTo evaluate sex differences and the relative effect of G2019S LRRK2 mutations in Parkinson's disease (PD).Methods530 LRRK2 PD carriers and 759 noncarrier PD (idiopathic, IPD) evaluated as part of the Fox Foundation (MJFF) Consortium were included. All participants completed a study visit including information on clinical features, treatment, examination, and motor and nonmotor questionnaires. Clinical features were compared between men and women separately for IPD and LRRK2 PD; and features were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 41 publications
(40 reference statements)
6
32
0
1
Order By: Relevance
“…In contrast, most studies of the association between urate and idiopathic PD when stratified by sex have observed reduced risk and slower progression with higher urate levels among men but not among women . The strength of the urate association observed in both women and men with LRRK2 mutations may help explain the comparable PD penetrance of LRRK2 mutations in women and men in both Ashkenazi Jewish (AJ) and non‐AJ LRRK2 + populations, in contrast to the well‐established lower risk of idiopathic PD in women . Because women have lower plasma urate levels than men, women may have a greater relative risk of PD in populations (like LRRK2 mutation carriers) in whom urate is associated with PD resistance in women as well as men.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, most studies of the association between urate and idiopathic PD when stratified by sex have observed reduced risk and slower progression with higher urate levels among men but not among women . The strength of the urate association observed in both women and men with LRRK2 mutations may help explain the comparable PD penetrance of LRRK2 mutations in women and men in both Ashkenazi Jewish (AJ) and non‐AJ LRRK2 + populations, in contrast to the well‐established lower risk of idiopathic PD in women . Because women have lower plasma urate levels than men, women may have a greater relative risk of PD in populations (like LRRK2 mutation carriers) in whom urate is associated with PD resistance in women as well as men.…”
Section: Discussionmentioning
confidence: 97%
“…Information about the TRACTS longitudinal study has been previously reported by McGlinchey et al [28] . For the PD population from the LRRK2 cohort, diagnostic instruments included the Montreal Cognitive Assessment (MoCA), the Unified Parkinson's Disease Rating Scale (UPDRS), the Geriatric Depression Scale (GDS) and the Non-Motor Symptoms (NMS) questionnaire, as was previously reported [29] . For all participants, informed consent and institutional review board approval was obtained at each site (TRACTS: VA Boston Institution Review Board #2345; PrecisionMED: Western Institutional Review Board® #2900; LRRK2: Tel Aviv Medical Center Ethical Committee; BioIVT: Western Institutional Review Board® #2010-017).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, some studies have found a higher prevalence of LRRK2 mutations among women than among men [12]. LRRK2 mutations also show sex-specific phenotypic effects, including milder motor symptoms and higher cognitive function, a lower incidence of REM sleep behavior disorder (RBD) and worse thermoregulation scores in men with LRRK2-G2019S mutation compared to men with iPD, whereas women with LRRK2-G2019S had worse motor complications than women with iPD [13]. In addition, among the patients with LRRK2 PD, women had worse motor complications but better olfaction than men.…”
Section: Introductionmentioning
confidence: 99%